Seismological constraints on the high-gravity DOV stars PG2131+066 and PG 1707+427 - Córsico, Alejandro Hugo (2009)
A seismological study of the pulsating PG1159 stars PG2131+066 and PG 1707+427 is presented. We perform extensive adiabatic computations of g-mode pulsation periods of PG1159 evolutionary models with stellar masses ranging from 0.530 to 0.741 M⊙. We constrain the stellar mass of PG2131+066 and PG 1707+427 by comparing the observed period spacing of each star with the theoretical asymptotic period spacings and with the average of the computed period spacings. We also employ the individual observed periods to find representative seismological models for both stars.